Digitalization of Vocational School Management: Challenges and Opportunities in Strengthening Educational Governance - Susanti; Dewi Cahyani; Muhammad Ali (al-Afkar, Journal For Islamic Studies, 2026)
This article examines the process of digitalization of management within vocational schools and its role in improving the quality of educational governance. Digital adoption is essential to ensure efficiency, transparency, and accountability in all aspects of school management, from student administration and curriculum management to human resources and school assets. Digitalization offers significant opportunities, such as streamlining administrative workflows, facilitating faster and more accurate data-driven decision-making, and strengthening collaboration between schools, industry, and parents. This directly contributes to the creation of educational governance that is far more adaptive and responsive to workplace needs.Digitalization of vocational school management is not only about utilizing technology for learning, but also encompasses restructuring governance, strengthening information systems, improving the competency of educators, and collaborating with data- and technology-driven industries. This study aims to comprehensively analyze the challenges and opportunities for digitalization of vocational school management in Indonesia through a systematic literature review of research conducted between 2022 and 2025.The study's findings indicate that key challenges include limited digital infrastructure, low digital literacy among education personnel, organizational cultural resistance, curriculum unpreparedness, inadequate sustainable funding, weak policies, and data security issues. However, digitalization offers significant opportunities in the form of administrative efficiency, governance transparency, improved technology-based learning, the establishment of a stronger industry partnership ecosystem, increased graduate employability, and data-driven decision-making. This article concludes that digitalization can only be successful if implemented through a comprehensive transformation strategy: infrastructure readiness, human resource development, robust national policy design, and ongoing evaluation. Recommendations for further research are also presented to enrich the direction of future vocational education transformation.